Thrombolytic Recanalization of Carotid Arteries Is Highly Dependent on Degree of Stenosis, Despite Sonothrombolysis. Issue 2 (February 2016) - Tomkins, Amelia J.; Hood, Rebecca J.; Pepperall, Debbie; Null, Christopher L.; Levi, Christopher R.; Spratt, Neil J.
Abstract : Background: Stroke associated with acute carotid occlusion is associated with poor effectiveness of tissue plasminogen activator (tPA) thrombolysis and poor prognosis. Rupture of atherosclerotic plaques resulting in vascular occlusions may occur on plaques, causing variable stenosis. We hypothesized that degree of stenosis may affect recanalization rates with tPA. Ultrasound+tPA (sonothrombolysis) has been shown to improve recanalization for intracranial occlusions but has not been tested for carotid occlusion. Our primary aim was to determine thrombolytic recanalization rates in a model of occlusion with variable stenosis, with a secondary aim to investigate sonothrombolysis in this model. Methods and Results: Rat carotid arteries were crushed and focal stenosis created (25% baseline Doppler flow) with a silk‐suture tie invoking thrombosis and occlusion. To model mild or severe stenosis, the tie was released pretreatment or left in place. Animals were treated with tPA (10 mg/kg) or tPA+ultrasound (2‐MHz) in each stenosis model (n=7/group). Recanalization was assessed by Doppler flow. Thrombolytic recanalization rates were significantly higher in mild stenosis groups (71% versus 0% with severe stenosis; P <0.0001). Recanalization rates were not significantly higher with additional ultrasound in either model. Conclusions: In this model, the degree of carotid stenosis had a large effect on thrombolytic recanalization. Sonothrombolysis using standard parameters for intracranial sonothrombolysis did not increase recanalization. Further testing is warranted. The degree of underlying stenosis may be an important predictor of thrombolytic recanalization, and clinical correlation of these findings may provide new approaches to treatment selection for patients with carotid occlusion.